Antiretroviral Therapy Initiation during Tuberculosis Treatment and HIV-RNA and CD4-T Lymphocyte Responses - Takuva, Simbarashe (2012)
SETTING AND OBJECTIVE: We examined the effect of initiating ART on CD4 and viral response at different time periods during TB therapy (< 14 days; 15–60 days; or ≥60 days) using prospectively collected clinical data from a large HIV clinic in South Africa. METHODS: Cohort data analysis for 1499 TB/HIV co-infected patients classified according to timing of ART after the initiation of TB therapy. RESULTS: In adjusted modified Poisson regression models, CD4 and viral responses showed no significant differences according to timing of ART initiation (failure to increase CD4 by 6 months, <14 days vs. >60 days: RR 1.02 (95% CI 0.85–1.22), 15–60 days vs. >60 days: RR 1.00 (95% CI 0.86–1.15); failure to suppress virus by 6 months, <14 days vs. >60 days: RR 0.98 (95% CI 0.59–1.63), 15–60 days vs. >60 days: RR 0.96 (95% CI 0.66–1.41) and viral rebound at 12 months, 14 days vs. >60 days: RR 1.43 (95% CI 0.50–4.12), 15–60 days vs. >60 days: RR 1.14 (95% CI 0.39–3.34). Similar estimates were found in analysis restricted to patients with severe immunosuppression. CONCLUSION: Concerns over the overlapping impact of TB treatment with ART on ART response should not be a reason to delay ART in patients with HIV-associated TB.